Biological nano waterproof fiber material and preparation method thereof

By combining modified nanocellulose and urea formaldehyde resin and other materials, chemical modification and mechanical treatment technology are used to prepare bionanowaterproof fiber materials with excellent waterproof performance and mechanical strength, solving the deformation problem caused by water absorption of fiberboards and achieving high efficiency , economical waterproofing effect and aesthetics improve.

CN119307111AInactive Publication Date: 2025-01-14ZHONGJI MUYU NEW MATERIAL TECH (SUZHOU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411271088.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the small density and large internal voids of fiberboard, it is easy to absorb moisture and lead to warping and deformation. The existing waterproofing measures such as slow drying speed of paint or affecting the resistance to deformation, resulting in a decrease in the strength and increase in the cost of fiberboard.

Method used

Modified nanocellulose is chemically modified by methyl trimethoxysilane, toluenesulfonyl chloride or acetic acid, combined with urea formaldehyde resin, polyethylene, epoxy resin and polyethylene wax to form a bio-nanowaterproof fiber material with hydrophobic properties. Prepared by chemical vapor deposition, mechanical ball milling and ultrasonic treatment.

Benefits of technology

It achieves excellent waterproof performance, high mechanical strength and good gloss of fiber materials, and does not require surface paint treatment, which improves the production efficiency and durability of fiberboard.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a biological nano waterproof fiber material and a preparation method thereof. The waterproof fiber material is applied to wood boards, building wood boards, floors and wallboards. The fiber material comprises the following components: 30-45 parts of modified nano cellulose, 18-26 parts of urea resin, 6-9 parts of polyethylene, 10-14 parts of epoxy resin, 5-7 parts of polyethylene wax, 4-8 parts of color paste, 4-6 parts of a curing agent and 3-7 parts of a coupling agent. Wherein methyl trimethoxy silane, toluenesulfonyl chloride or acetic acid is adopted to carry out chemical modification on the nano cellulose to obtain the modified nano cellulose. The fiber material prepared by the preparation method disclosed by the invention has excellent waterproof performance, high mechanical strength and good glossiness, boards such as wood boards, building wood boards, floors and wallboards made of the fiber material do not need to be subjected to surface painting treatment for waterproofing, and the popularization prospect is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber materials, in particular to a biological nano waterproof fiber material, and also to a preparation method of the fiber material. Background Art

[0002] Fiberboard, also known as density board, is a man-made board made of plant fiber as raw material, urea-formaldehyde resin or other suitable adhesives, and through processes such as fiber separation, molding, drying and hot pressing. Additives can be added during the manufacturing process. Fiberboard has the advantages of uniform material, small vertical and horizontal strength difference and not easy to crack, and has a wide range of uses. 3 Fiberboard requires about 2.5 to 3 meters 3 of wood, can replace 3m 3 Sawn timber or 5m 3 Logs, therefore, developing fiberboard production is an effective way to comprehensively utilize wood resources.

[0003] However, fiberboard has a low density and large internal voids, so it is easy to absorb moisture. After absorbing moisture, the board will warp and deform due to the difference in expansion force. The board will become fragile, lose strength, and be easily damaged or even cracked. There are two common waterproofing measures at present. One is to apply waterproof paint on the surface of the fiberboard, but the paint has the problems of slow drying speed and easy aging, and increases the process flow of the fiberboard, affecting the production efficiency and cost of the fiberboard; the other is to add moisture-proof agent, but the use of moisture-proof agent will affect the board's ability to resist deformation, resulting in poor quality and durability of the fiberboard. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a bionano waterproof fiber material and a preparation method thereof to prepare a fiber material with excellent waterproof performance, high mechanical strength and good gloss.

[0005] A biological nano waterproof fiber material, the fiber material has the following components: 30-45 parts of modified nano cellulose, 18-26 parts of urea-formaldehyde resin, 6-9 parts of polyethylene, 10-14 parts of epoxy resin, 5-7 parts of polyethylene wax, 4-8 parts of color paste, 4-6 parts of curing agent, 3-7 parts of coupling agent; wherein the modified nano cellulose is obtained by chemically modifying the nano cellulose with methyltrimethoxysilane, toluenesulfonyl chloride or acetic acid.

[0006] In one embodiment, when methyltrimethoxysilane is used to chemically modify nanocellulose, the specific operation is as follows: methyltrimethoxysilane is used to modify nanocellulose using chemical vapor deposition to obtain modified nanocellulose with hydrophobic properties. In the present invention, silane has a strong affinity with hydroxyl groups and can interact with the hydroxyl groups on nanocellulose, thereby constructing a stable hydrophobic three-dimensional network structure in the form of -Si-O-C- on the surface of nanocellulose.

[0007] In one embodiment, when toluenesulfonyl chloride is used to chemically modify nanocellulose, the specific operation is as follows: in the presence of a small amount of catalyst, acetic anhydride and toluenesulfonyl chloride are added to react with nanocellulose to obtain modified nanocellulose with hydrophobic properties. In the present invention, sulfuric acid or perchloric acid is used as the catalyst, and toluenesulfonyl chloride is introduced to convert the exposed hydroxyl groups on the surface of nanocellulose into -COCH 3 , thus changing the hydrophilicity of nanocellulose to hydrophobicity.

[0008] In one embodiment, when acetic acid is used to chemically modify nanocellulose, the specific operation is as follows: acetic acid is dispersed in an aqueous medium based on ultrasonic treatment, and acetic acid reacts with hydroxyl groups on the surface of nanocellulose at 200-240°C and 80-100kPa to obtain modified nanocellulose with hydrophobic properties. In the present invention, the exposed hydroxyl groups on the surface of nanocellulose are converted into ester groups through esterification reaction, thereby obtaining modified nanocellulose with strong mechanical properties.

[0009] In one embodiment, the mass ratio of the modified nanocellulose, urea-formaldehyde resin, polyethylene and epoxy resin is 3-9:2-5:1:1-3; the mass content of polyethylene wax in the fiber material is 5%-7%. In the present invention, polyethylene is added as a filler to save the amount of resin, and is compounded with the modified nanocellulose to improve the mechanical strength of the fiber material.

[0010] Preferably, the fiber material has the following components: 40 parts of modified nanocellulose, 24 parts of urea-formaldehyde resin, 8 parts of polyethylene, 13 parts of epoxy resin, 6 parts of polyethylene wax, 7 parts of color paste, 5 parts of curing agent, and 6 parts of coupling agent. In the present invention, polyethylene wax is added to promote the mutual melting and anti-sticking properties between the resin materials (urea-formaldehyde resin + epoxy resin), and at the same time has good dispersion properties for modified nanocellulose, polyethylene, color paste, curing agent and coupling agent, so that the mixed system is uniform, thereby improving the gloss of the fiber material, so that the board made of the fiber material has the advantages of high surface finish and good aesthetics.

[0011] Preferably, the curing agent is any one of vinyl triamine, diamino cyclohexane, methylene biscyclohexane amine and diethylene triamine benzidine. In the present invention, the color paste plays a role in adjusting the color of the material so that the obtained artificial board has the color of the natural board, and the curing agent plays a role in adjusting the curing process of the material.

[0012] Preferably, the coupling agent is a silane coupling agent, a titanate coupling agent or an aluminate coupling agent. In the present invention, the coupling agent plays a role in improving the interface properties between various components and enhancing the overall performance of the material.

[0013] A method for preparing a fiber material, which is used to prepare the biological nano waterproof fiber material, and the preparation method comprises the following steps:

[0014] S1: urea-formaldehyde resin, polyethylene and epoxy resin are subjected to mechanical ball milling to obtain a mixed powder for later use;

[0015] S2: crush and pulp the natural biomaterial, mix it with polyvinyl alcohol, and then send it into an extruder to melt and extrude it into a melt-blowing device, and obtain nanocellulose under the traction of a hot air flow, and then chemically modify it to obtain modified nanocellulose;

[0016] S3: Mix the mixed powder and modified nanocellulose, then add polyethylene wax, color paste, curing agent and coupling agent to obtain bio-nano waterproof fiber material through mixing treatment.

[0017] Preferably, the mechanical ball milling treatment is carried out in a ball mill, the ball milling speed is 300-400 r / min, and the ball milling time is 3-5 hours. In the present invention, a uniform and fine mixed powder is obtained by ball milling treatment.

[0018] Preferably, the natural biological material is trees, plants or waste wood; the fiber diameter of the nanocellulose is 20 to 50 nm. The present invention uses natural biological materials to prepare nanocellulose, so that the nanocellulose can be recycled and biodegraded. In addition, nanocellulose has the characteristics of low density and high strength, and is strong and durable. In addition, nanocellulose has small particle size, large surface area, many hydroxyl groups on the surface, and is easy to combine with other atoms. It can be modified to obtain a composite material, and its application field is expanded.

[0019] Preferably, the mixing process is carried out in an internal mixer, and the working speed of the internal mixer is 20-50 r / min, the mixing time is 15-20 min, and the mixing temperature is 150-170°C.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention uses natural biological materials to prepare nanocellulose, so that the nanocellulose can be recycled and biodegraded. In addition, the nanocellulose has the characteristics of low density and high strength, and is strong and durable. In addition, the nanocellulose has the characteristics of small particle size, large surface area, many hydroxyl groups on the surface, and easy to combine with other atoms. Hydrophobic groups are introduced through modification, so that the fiber material itself has excellent waterproof performance. When used on a board, there is no need for surface painting, and the promotion prospect is excellent.

[0022] In the present invention, polyethylene is added as a filler to save the amount of resin, and is compounded with modified nanocellulose to improve the mechanical strength of the fiber material. At the same time, modified nanocellulose and epoxy resin are blended for toughening modification, and the two have good compatibility, thereby improving the mechanical strength of the fiber material.

[0023] The invention adds polyethylene wax to promote the mutual solubility and anti-stickiness between resin materials (urea-formaldehyde resin+epoxy resin), and at the same time has good dispersion performance for modified nano cellulose, polyethylene, color paste, curing agent and coupling agent, so that the mixed system is uniform, thereby improving the glossiness of the fiber material, so that the board made of the fiber material has the advantages of high surface finish and good aesthetics. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.

[0025] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0026] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values ​​and all integers and fractions within the range.

[0027] The specific embodiments of the present invention are described in detail below.

[0028] Example 1

[0029] The present embodiment provides a bio-nano waterproof fiber material, which has the following components: the fiber material has the following components: 30 parts of modified nano cellulose, 18 parts of urea-formaldehyde resin, 6 parts of polyethylene, 10 parts of epoxy resin, 5 parts of polyethylene wax, 4 parts of color paste, 4 parts of vinyltriamine, and 3 parts of silane coupling agent.

[0030] The modified nanocellulose is obtained by chemically modifying nanocellulose with methyltrimethoxysilane, and the specific operation is as follows: the nanocellulose is modified with methyltrimethoxysilane by chemical vapor deposition to obtain modified nanocellulose with hydrophobic properties. In the present invention, silane has a strong affinity with hydroxyl groups and can interact with the hydroxyl groups on the nanocellulose, thereby constructing a stable hydrophobic three-dimensional network structure in the form of -Si-O-C- on the surface of the nanocellulose.

[0031] The preparation method of the waterproof fiber material of this embodiment includes the following steps:

[0032] S1: urea-formaldehyde resin, polyethylene and epoxy resin are subjected to mechanical ball milling to obtain a mixed powder for later use;

[0033] S2 takes trees and crushes them for pulping, mixes them with polyvinyl alcohol, and then feeds them into an extruder for melting and extrusion to a melt-blowing device, where nanocellulose with a fiber diameter of 20 nm is obtained under the traction of a hot air flow, and then chemically modified to obtain modified nanocellulose. The mechanical ball milling treatment is carried out in a ball mill at a ball milling speed of 300 r / min and a ball milling time of 5 h.

[0034] S3: Mix the mixed powder and modified nanocellulose, then add polyethylene wax, color paste, ethylene triamine and silane coupling agent, and mix them to obtain a biological nano waterproof fiber material. The mixing process is carried out in an internal mixer, and the working speed of the internal mixer is 20 r / min, the mixing time is 20 min, and the mixing temperature is 150° C.

[0035] Example 2

[0036] The present embodiment provides a bio-nano waterproof fiber material, which has the following components: 35 parts of modified nano cellulose, 20 parts of urea-formaldehyde resin, 7 parts of polyethylene, 11 parts of epoxy resin, 6 parts of polyethylene wax, 5 parts of color paste, 5 parts of diaminocyclohexane, and 4 parts of titanate coupling agent.

[0037] The modified nanocellulose is obtained by chemically modifying the nanocellulose with toluenesulfonyl chloride. The specific operation is as follows: in the presence of a small amount of catalyst, acetic anhydride and toluenesulfonyl chloride are added to react with the nanocellulose to obtain the modified nanocellulose with hydrophobic properties. In the present invention, sulfuric acid or perchloric acid is used as the catalyst. By introducing toluenesulfonyl chloride, the exposed hydroxyl groups on the surface of the nanocellulose are converted into -COCH 3 , thus changing the hydrophilicity of nanocellulose to hydrophobicity.

[0038] The preparation method of the waterproof fiber material of this embodiment includes the following steps:

[0039] S1: urea-formaldehyde resin, polyethylene and epoxy resin are subjected to mechanical ball milling to obtain a mixed powder for later use;

[0040] S2 takes the plant and crushes it, mixes it with polyvinyl alcohol, and then feeds it into an extruder to melt and extrude it into a melt-blowing device, and obtains nanocellulose with a fiber diameter of 30 nm under the traction of a hot air flow, and then chemically modifies it to obtain modified nanocellulose. The mechanical ball milling treatment is carried out in a ball mill, the ball milling speed is 350 r / min, and the ball milling time is 4 hours.

[0041] S3: Mix the mixed powder and modified nanocellulose, then add polyethylene wax, color paste, diaminocyclohexane and titanate coupling agent, and mix them to obtain a bio-nano waterproof fiber material. The mixing process is carried out in an internal mixer, and the working speed of the internal mixer is 30r / min, the mixing time is 17min, and the mixing temperature is 160°C.

[0042] Example 3

[0043] The present embodiment provides a bio-nano waterproof fiber material, which has the following components: 40 parts of modified nanocellulose, 24 parts of urea-formaldehyde resin, 8 parts of polyethylene, 13 parts of epoxy resin, 6 parts of polyethylene wax, 7 parts of color paste, 5 parts of diethylenetriaminebenzidine, and 6 parts of titanate coupling agent.

[0044] The modified nanocellulose is obtained by chemically modifying the nanocellulose with acetic acid, and the specific operation is as follows: the acetic acid in the aqueous medium is dispersed based on ultrasonic treatment, and the acetic acid reacts with the hydroxyl groups on the surface of the nanocellulose at 220°C and 90kPa to obtain the modified nanocellulose with hydrophobic properties. In the present invention, the exposed hydroxyl groups on the surface of the nanocellulose are converted into ester groups through the esterification reaction, thereby obtaining the modified nanocellulose with strong mechanical properties.

[0045] The preparation method of the waterproof fiber material of this embodiment includes the following steps:

[0046] S1: urea-formaldehyde resin, polyethylene and epoxy resin are subjected to mechanical ball milling to obtain a mixed powder for later use;

[0047] S2 takes trees and crushes them for pulping, mixes them with polyvinyl alcohol, and then feeds them into an extruder for melting and extrusion to a melt-blowing device, where nanocellulose with a fiber diameter of 40 nm is obtained under the traction of a hot air flow, and then chemically modified to obtain modified nanocellulose. The mechanical ball milling treatment is carried out in a ball mill at a ball milling speed of 380 r / min and a ball milling time of 4.5 h.

[0048] S3: Mix the mixed powder and modified nanocellulose, then add polyethylene wax, color paste, diethylenetriamine benzidine and titanate coupling agent, and mix them to obtain a bio-nano waterproof fiber material. The mixing process is carried out in an internal mixer, and the working speed of the internal mixer is 40r / min, the mixing time is 19min, and the mixing temperature is 165°C.

[0049] Example 4

[0050] The present embodiment provides a bio-nano waterproof fiber material, which has the following components: 45 parts of modified nanocellulose, 26 parts of urea-formaldehyde resin, 9 parts of polyethylene, 14 parts of epoxy resin, 7 parts of polyethylene wax, 8 parts of color paste, 6 parts of solid methylene dicyclohexane amine, and 7 parts of aluminate coupling agent.

[0051] The modified nanocellulose is obtained by chemically modifying the nanocellulose with acetic acid, and the specific operation is as follows: the acetic acid in the aqueous medium is dispersed based on ultrasonic treatment, and the acetic acid reacts with the hydroxyl groups on the surface of the nanocellulose at 240°C and 100kPa to obtain the modified nanocellulose with hydrophobic properties. In the present invention, the exposed hydroxyl groups on the surface of the nanocellulose are converted into ester groups through the esterification reaction, thereby obtaining the modified nanocellulose with strong mechanical properties.

[0052] The preparation method of the waterproof fiber material of this embodiment includes the following steps:

[0053] S1: urea-formaldehyde resin, polyethylene and epoxy resin are subjected to mechanical ball milling to obtain a mixed powder for later use;

[0054] S2 takes waste wood and crushes it for pulping, mixes it with polyvinyl alcohol, and then feeds it into an extruder for melting and extrusion to a melt-blowing device, and obtains nanocellulose with a fiber diameter of 50 nm under the traction of a hot air flow, and then chemically modifies it to obtain modified nanocellulose. The mechanical ball milling treatment is carried out in a ball mill, the ball milling speed is 400 r / min, and the ball milling time is 5 h.

[0055] S3: Mix the mixed powder and modified nanocellulose, then add polyethylene wax, color paste, methylenebiscyclohexaneamine and aluminate coupling agent, and mix them to obtain a bionano waterproof fiber material. The mixing process is carried out in an internal mixer, and the working speed of the internal mixer is 50r / min, the mixing time is 20min, and the mixing temperature is 170°C.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 3 is that polyethylene is not added. The rest is the same as Example 3.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 3 is that nano-wood fiber is used instead of modified nano-cellulose. The rest is the same as Example 3.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 3 is that no polyethylene wax is added. The rest is the same as Example 3.

[0062] The present invention uses natural biological materials to prepare nanocellulose, so that the nanocellulose can be recycled and biodegraded. In addition, the nanocellulose has the characteristics of low density and high strength, and is strong and durable. In addition, the nanocellulose has the characteristics of small particle size, large surface area, many hydroxyl groups on the surface, and easy to combine with other atoms. Hydrophobic groups are introduced through modification, so that the fiber material itself has excellent waterproof performance. When used on a board, there is no need for surface painting, and the promotion prospect is excellent.

[0063] In the present invention, polyethylene is added as a filler to save the amount of resin, and is compounded with modified nanocellulose to improve the mechanical strength of the fiber material. At the same time, modified nanocellulose and epoxy resin are blended for toughening modification, and the two have good compatibility, thereby improving the mechanical strength of the fiber material.

[0064] The invention adds polyethylene wax to promote the mutual solubility and anti-stickiness between resin materials (urea-formaldehyde resin+epoxy resin), and at the same time has good dispersion performance for modified nano cellulose, polyethylene, color paste, curing agent and coupling agent, so that the mixed system is uniform, thereby improving the glossiness of the fiber material, so that the board made of the fiber material has the advantages of high surface finish and good aesthetics.

[0065] The fiber materials of Examples 1 to 4 and Comparative Examples 1 to 3 were used to prepare artificial boards, and then the waterproofness, mechanical strength and glossiness were tested. The specific board production process is as follows: the fiber material is transported to an extruder, squeezed into a mold and shaped at 200°C, then water-cooled, pulled out and coated, and finally cut to obtain a board.

[0066] The above specific detection process is not described in detail here, and the detection results are shown in Table 1.

[0067] Table 1

[0068] Waterproof Mechanical strength (MPa) Glossiness Example 1 Level 4-5 50 Excellent Example 2 Level 4-5 53 Excellent Example 3 Level 5 56 Excellent Example 4 Level 4-5 52 Excellent Comparative Example 1 Level 4 25 good Comparative Example 2 Level 2 40 good Comparative Example 3 Level 3-4 50 Difference

[0069] Note: In Table 1, the higher the grade among grades 1 to 5, the better the waterproofness.

[0070] The above test results prove that the fiber material prepared by the preparation method of the present invention has excellent waterproof performance, high mechanical strength and good gloss. Boards such as wood boards, building boards, floors and wall panels made of the fiber material do not need to be waterproofed by surface painting and have excellent promotion prospects.

[0071] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A bionano waterproof fiber material, characterized in that: The fiber material has the following components: 30-45 parts of modified nanocellulose, 18-26 parts of urea-formaldehyde resin, 6-9 parts of polyethylene, 10-14 parts of epoxy resin, 5-7 parts of polyethylene wax, 4-8 parts of color paste, 4-6 parts of curing agent, and 3-7 parts of coupling agent; The modified nanocellulose is obtained by chemically modifying the nanocellulose with methyltrimethoxysilane, toluenesulfonyl chloride or acetic acid.

2. The bionano waterproof fiber material according to claim 1, characterized in that: When methyltrimethoxysilane is used to chemically modify nanocellulose, the specific operation is as follows: nanocellulose is modified with methyltrimethoxysilane using chemical vapor deposition to obtain modified nanocellulose with hydrophobic properties.

3. The bionano waterproof fiber material according to claim 1, characterized in that: When toluenesulfonyl chloride is used to chemically modify nanocellulose, the specific operation is as follows: in the presence of a small amount of catalyst, acetic anhydride and toluenesulfonyl chloride are added to react with nanocellulose to obtain modified nanocellulose with hydrophobic properties.

4. The bionano waterproof fiber material according to claim 1, characterized in that: When acetic acid is used to chemically modify nanocellulose, the specific operation is as follows: the acetic acid in the aqueous medium is dispersed based on ultrasonic treatment, and the acetic acid undergoes an esterification reaction with the hydroxyl groups on the surface of the nanocellulose at 200-240°C and 80-100kPa to obtain modified nanocellulose with hydrophobic properties.

5. The bionano waterproof fiber material according to claim 1, characterized in that: The mass ratio of the modified nanocellulose, urea-formaldehyde resin, polyethylene and epoxy resin is 3-9:2-5:1:1-3; The mass content of the polyethylene wax in the fiber material is 5% to 7%.

6. The bionano waterproof fiber material according to claim 5, characterized in that: The fiber material has the following components: 40 parts of modified nanocellulose, 24 parts of urea-formaldehyde resin, 8 parts of polyethylene, 13 parts of epoxy resin, 6 parts of polyethylene wax, 7 parts of color paste, 5 parts of curing agent, and 6 parts of coupling agent.

7. The bionano waterproof fiber material according to claim 6, characterized in that: The curing agent is any one of vinyltriamine, diaminocyclohexane, methylenebiscyclohexaneamine and diethylenetriaminebenzidine; The coupling agent is a silane coupling agent, a titanate coupling agent or an aluminate coupling agent.

8. A method for preparing a fiber material, which is used to prepare the bio-nano waterproof fiber material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1: urea-formaldehyde resin, polyethylene and epoxy resin are subjected to mechanical ball milling to obtain a mixed powder for later use; S2: crush and pulp the natural biomaterial, mix it with polyvinyl alcohol, and then send it into an extruder to melt and extrude it into a melt-blowing device, and obtain nanocellulose under the traction of a hot air flow, and then chemically modify it to obtain modified nanocellulose; S3: Mix the mixed powder and modified nanocellulose, then add polyethylene wax, color paste, curing agent and coupling agent to obtain bio-nano waterproof fiber material through mixing treatment.

9. The method for preparing the fiber material according to claim 8, characterized in that: The mechanical ball milling treatment is carried out in a ball mill, the ball milling speed is 300-400 r / min, and the ball milling time is 3-5 h; The natural biological material is trees, plants or waste wood; the fiber diameter of the nanocellulose is 20-50nm.

10. The method for preparing the fiber material according to claim 9, characterized in that: The mixing process is carried out in an internal mixer, and the working speed of the internal mixer is 20-50 r / min, the mixing time is 15-20 min, and the mixing temperature is 150-170° C.

Citation Information

Patent Citations

  • Resin composition

    JP2012229350A

  • Slidable resin composition

    JP2017171698A

  • Master batch composition suitable for fiber-reinforced resin and method for producing fiber-reinforced resin

    JP2023014761A

  • resin composition

    JP6189558B1

  • Method for Preparing Cellulose Nanofiber Capable of Being Stably Dispersed

    US20140299019A1